Professional development as viewed by EFL teachers at lower secondary schools - Rachmajanti, Sri; Sulistyo, Gunadi Harry; Megawati, Fika; Akbar, Ayu Alif Nur Maharani (Universitas Muhammadiyah Sidoarjo, 2020)
In the developed world, teachers are compelled to be professional in handling instructional process for students’ optimum learning. There are many ways for teacher professionalism. This study deals with an exploratory survey to probe EFL teachers’ views of teacher professionalism at the public and private lower secondary levels of education on the areas for professional development or learning. A number of 302 EFL teachers of the lower secondary level of education are conveniently drawn from a number of cities/regencies as samples of the present study representing EFL teachers with diverse teaching experiences in East Java. A questionnaire was developed to collect data on their ideas connected with aspects of developing themselves professionally. The results of the present study are discussed pertaining to EFL teacher normative responsibilities and concepts on professional development/learning. Pedagogical and theoretical implications of the findings are drawn with reference to the context of English instruction.